S670, an amide derivative of 3-O-acetyl-11-keto-β-boswellic acid, induces ferroptosis in human glioblastoma cells by generating ROS and inhibiting STX17-mediated fusion of autophagosome and lysosome - Yang Yi-hui; Li Wan; Ren Li-wen; Yang Hong; Zhang Yi-zhi; Zhang Sen; Hao Yue; Yu Dong-ke; Tong Rong-sheng; Du Guan-hua; Shi Jian-you; Wang Jin-hua (Acta Pharmacologica Sinica, 2023)
Glioblastoma (GBM) is the most common malignant tumor in the brain with temozolomide (TMZ) as the only approved chemotherapy agent. GBM is characterized by susceptibility to radiation and chemotherapy resistance and recurrence as well as low immunological response. There is an urgent need for new therapy to improve the outcome of GBM patients. We previously reported that 3-O-acetyl-11-keto-β-boswellic acid (AKBA) inhibited the growth of GBM. In this study we characterized the anti-GBM effect of S670, a synthesized amide derivative of AKBA, and investigated the underlying mechanisms. We showed that S670 dose-dependently inhibited the proliferation of human GBM cell lines U87 and U251 with IC50 values of around 6 μM. Furthermore, we found that S670 (6 μM) markedly stimulated mitochondrial ROS generation and induced ferroptosis in the GBM cells. Moreover, S670 treatment induced ROS-mediated Nrf2 activation and TFEB nuclear translocation, promoting protective autophagosome and lysosome biogenesis in the GBM cells. On the other hand, S670 treatment significantly inhibited the expression of SXT17, thus impairing autophagosome-lysosome fusion and blocking autophagy flux, which exacerbated ROS accumulation and enhanced ferroptosis in the GBM cells. Administration of S670 (50 mg·kg−1·d−1, i.g.) for 12 days in a U87 mouse xenograft model significantly inhibited tumor growth with reduced Ki67 expression and increased LC3 and LAMP2 expression in the tumor tissues. Taken together, S670 induces ferroptosis by generating ROS and inhibiting STX17-mediated fusion of autophagosome and lysosome in GBM cells. S670 could serve as a drug candidate for the treatment of GBM.